2005
DOI: 10.1007/s10789-005-0128-7
|View full text |Cite
|
Sign up to set email alerts
|

Doping of optical fiber preforms via porous silica layer infiltration with salt solutions

Abstract: A process is described for reproducible deposition of porous layers uniform along the preform axis, and the effect of the nature of the solvent on the infiltration of salt solutions into the porous layer is analyzed in relation to the fabrication of fiber preforms with controlled doping level. Data are presented on the variation of the retention volume in the porous layer with sintering temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Recently, Khopin et al [10] have studied solution retention in a porous soot layer as a function of the deposition temperature and the soot layer composition. Partial sintering of the soot occurred immediately after deposition, so that the solution was less able to penetrate the soot layer.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Khopin et al [10] have studied solution retention in a porous soot layer as a function of the deposition temperature and the soot layer composition. Partial sintering of the soot occurred immediately after deposition, so that the solution was less able to penetrate the soot layer.…”
Section: Introductionmentioning
confidence: 99%
“…The surface tension of fixed strength of aqueous solution selected for the study is found to be 2 to 3 times higher than that of the ethanolic solution. It has been reported [Khopin et al 2005] Thus lower surface tension as well as smaller complex size of dopant ions are responsible for faster soaking in case of ethanolic solution compared to same strength of aqueous solution when soaked for fixed time span. The investigation reveals that solvent plays an important role in controlling incorporation of RE ion in fiber.…”
Section: Selected Solvent Vs Re Incorporation Levelmentioning
confidence: 99%
“…With the aim of producing active optical fibers with an increased rare-earth concentration in the core, we examined the possibility of doping silica glass with alumina using a two-step MCVD process: deposition of a porous layer which is then infiltrated with a precursor salt solution [13]. As the precursor, we used aluminum nitrate, which is readily soluble in water and alcohols.…”
Section: Optimization Of the Core Compositionmentioning
confidence: 99%
“…As seen in Fig. 1, the alumina content of the glass can be brought to 3.5-4.0 mol %, using the optimal temperature for sintering the porous layer [13].…”
Section: Optimization Of the Core Compositionmentioning
confidence: 99%